DETERMINATION OF LANDSLIDE SLIP PLANE USING GEOLOGY AND GEOELECTRICAL ANALYSIS AT MOUNT GEGER PULUS LEGOK EMO SLOPE SEGMENT, CILILIN, WEST JAVA - Iwan Gunawan Tejakusuma (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2020)
Mount Geger Pulus in Cililin District, West Java shows a cone geomorphology composed of an Andesitic intrusion in which part of the slope is covered by volcanic rock. Small scale landslides have occurred several times indicating that the surrounding area is at risk of landslides. The slope segment of Legok Emo of this mount has a steep to very steep slope, covered by secondary and mixed forests. Settlement lies around the bottom of this slope. The results of geoelectrical measurements and geological analysis of this slope segment indicate that the slope has a potential to landslide that is controlled by tuff acting as a slip plane and can be triggered by rainfall. The layer that has the potential to landsliding are weathered volcanic breccias with a thickness of about 3 meters with a maximum of 5 meters that is overlying tuff which is relatively impermeable.